Electrodeposition-based in situ construction of a ZnO-ordered macroporous film gas sensor with enhanced sensitivity. Issue 3 (2nd January 2019) - Pan, Zizhao; Sun, Fengqiang; Zhu, Ximiao; Chen, Zhicong; Lin, Xi; Zheng, Yujian; Zhong, Wenyu; Zhuang, Zefeng; Gu, Fenglong
Abstract : A ZnO-ordered macroporous film sensor integrated with standing nanosheets was in situ constructed based on electrodeposition, and exhibited enhanced sensitivity to ethanol gas. Abstract : The in situ construction of gas sensors is of great significance to obtain the desired structure of a sensing film with enhanced performance. In this work, an electrodeposition-based method was employed to in situ construct a ZnO-ordered macroporous film resistive-type gas sensor for the first time. A ceramic tube was used as the substrate and coated with graphite as an auxiliary conductive layer. By electrodeposition co-induced by a two-dimensional colloidal crystal template and sodium dodecylsulfate, metallic Zn standing nanosheets and Zn(OH)2 shells were grown around template microspheres. Then, by heat treatment in air, a ZnO-ordered macroporous film gas sensor was obtained. The film possessed a novel and unique structure composed of a monolayer macropore array and standing nanosheets integrated into the interstices among the macropores. The growth of pore-walls and nanosheets, as well as the morphology and sensing response of the final film, is controlled by the electrodeposition time. Given the synergy between the macroporous structure and the standing nanosheets, the sensing response of this ZnO film to ethanol gas was considerably enhanced compared with that of the film with only a macroporous structure, the film with only standing nanosheets, and the film without these two structures. Moreover, the sensor also exhibited a ppb-level detection limit, excellent reversibility, long-term stability and good selectivity. This method provides new approaches for constructing gas sensors with a uniform surface morphology and obtaining high sensing performance by constructing an ordered collocated structure.